Enacting Civility Through Comic Opera; or, Nation, Race, and Ned McGowan's War. (February 2016) - Davis-Fisch, Heather
Popular historians have frequently described the strange events now known as Ned McGowan's War in theatrical terms, specifically as comic opera. By taking up June Schlueter's suggestion that "virtually all" definitions of genre "have rested their case on the ending, " this essay considers how the "generic end" of this comic opera "pointedly involves itself in ideological concerns" by examining the social world that emerges via the climax and denouement of the "War." Considering the fears of American annexation and occupation that motivated the colonial response to the "War, " its "happy" ending reveals a highly unstable relationship between civil action and national identity at this particular moment. By considering what—and specifically who—fails to be incorporated into the world that emerges at the end of the comic opera, this essay argues that emergent notions of "white civility" in the colony relied on the drawing of and policing of strategic boundaries, in this case along not national but racial lines. The "War" was comprised of social performances which reveal not only the extent to which colonial British Columbia was a "performing society" but also that the boundaries of civil society were negotiated through theatricalized social performances.